Dampak Hasil Belajar Keaksaraan Usaha Mandiri dalam Menumbuhkan Sikap Berwirausaha Warga Belajar di PKBM Al-Muttaqin Jember - Aprillia Bunga Fatimah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The Keaksaraan Usaha Mandiri Program at PKBM Al-Muttaqin is designed to enhance learners' knowledge, attitudes, and skills, particularly in the context of entrepreneurship. This study aims to define the impact of the program's learning outcomes in fostering entrepreneurial attitudes among learners at PKBM AlMuttaqin, Jember, using a qualitative descriptive research method. Informants were selected using a purposive sampling technique, and data validity was achieved by employing strategies such as prolonged observation, enhanced persistence, and triangulation of sources and techniques. The Miles and Huberman method was used for data analysis, consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that the Keaksaraan Usaha Mandiri Program contributed to learners' abilities in food product processing, which subsequently improved their quality of life. This improvement was reflected in more active participation in community activities and the initiation of small-scale independent businesses. The program’s impact extended beyond practical skill development, fostering an entrepreneurial attitude among participants. Learners demonstrated increased self-confidence, a greater focus on task completion and achieving results, and a higher readiness to take calculated risks. These findings highlight the program’s role in equipping learners with the necessary skills to navigate uncertainties in the business world. Overall, the program not only enhanced learners' knowledge, attitudes, and practical skills but also fostered an entrepreneurial attitude that emphasizes continuous improvement and effective problem-solving in business pursuits.
Entry oleh Arif 2026 Maret 26
Keywords: Keaksaraan Usaha Mandiri; Entrepreneurial Attitudes; Learners